Diseño de un centro de experiencias turísticas en la comunidad de Zuleta, parroquia rural Angochagua - Valencia Aguirre, Amparo Estefanía (2023)
The TT is based in the Zuleta Community, a rural Angochagua parish located 40 minutes from the city of Ibarra, It is an ideal place to integrate its natural landscapes with society, seeing from the eyes of the community, starting with its history, surrounded by cultural customs and traditions that over time it dissipates and transforms to be accepted by new interests\; Active tourism, after a global pandemic this community takes powerful turn, being a potential attraction for families looking for an open and safe place. Zuleta recognized nationally and internationally for its embroidery and crafts, has endless natural attractions, from its landscapes, flora, and fauna to its beautiful lagoons and moors, taking into account each of its potentials, a Tourist Experience Center is proposed, where the user can understand the day to day life of a person in this community and appreciate the effort they make to sustain themselves, the connection with nature is essential, making this facility a flexible and open space. The equipment has accommodation, gastronomy, education, leisure, and entertainment areas in order to attract users of all ages and with different types of interests, thanks to a modular architecture with low environmental impact that converges with nature. and be part of the community.